Field epidemiological investigation of a varicella outbreak in a school of Nanxun District， Huzhou - PENG Caiwei; YANG Liping; LIU Binhui (Shanghai yufang yixue, 2022)
ObjectiveTo determine the epidemiological characteristics and transmission factors of a varicella outbreak in a school in Nanxun District of Huzhou City， and assess the effect of prevention and control measures， which may provide scientific evidence for improvement in the response to varicella outbreak.MethodsData were collected by field epidemiological survey and analyzed by descriptive epidemiology. Statistical analysis was performed by SPSS 22.0 software.ResultsA total of 80 varicella cases were identified in this outbreak， which lasted 68 days. There were four peaks of incidence， involving 21 classes. The total incidence rate was determined to be 4.14%. Before the public health intervention， some cases were not isolated in time， which led to the initial spread in the class. After the mid-term examination， the outbreak further spread to multiple classes. Breakthrough varicella cases accounted for 48.75% of all the cases in the outbreak， among which 94.87% had been vaccinated for more than five years. However， there was no significant difference in the incidence of fever and rash between the breakthrough cases and non-breakthrough cases（P>0.05）.ConclusionTimely report， prompt response， and strict implementation of prevention and control measures remain crucial for effective containment of varicella outbreak.